Numerical modeling of the beach process of marine plastics: A probabilistic and diagnostic approach with a particle tracking method. (March 2020) - Hinata, Hirofumi; Sagawa, Nao; Kataoka, Tomoya; Takeoka, Hidetaka
Abstract: A model of the beach process of marine plastics was proposed based on the assumption of the beaching and backwashing flux balance, and its applicability was examined by means of time-invariant linear system analysis and particle tracking experiments with respect to the ratio between the residence time of plastics on a beach ( τ r ) and the period of nearshore current variability ( T 0 ). Based on the theory, the balance was expected to hold when τ r / T 0 was much smaller than 1; however, good agreement was obtained between the theory and the particle tracking method for much larger values of τ r / T 0 . The parameters, which are diagnostically given in the model, will be prognostically decided by the coastal dynamics in the future to develop robust beach process models. Nevertheless, we believe that a diagnostic approach would be another pillar in the strategy for estimating the amounts and distributions of marine plastics in the coming years. Highlights: A beach process model of marine plastics for micro- to macroplastics was proposed. The model was based on the assumption of the beaching and backwashing flux balance. The model was validated by a linear system theory and particle tracking experiments. The model allows us to examine the seasonal to interannual variabilities of plastics.